2001
DOI: 10.1590/s0100-879x2001000100014
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of lead and zinc on inhibitory avoidance learning in mice

Abstract: We studied the effects of chronic intoxication with the heavy metals lead (Pb 2+ ) and zinc (Zn 2+ ) on memory formation in mice. Animals were intoxicated through drinking water during the pre-and postnatal periods and then tested in the step-through inhibitory avoidance memory task. Chronic postnatal intoxication with Pb 2+ did not change the step-through latency values recorded during the 4 weeks of the test (ANOVA, P>0.05). In contrast, mice intoxicated during the prenatal period showed significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
2
9
0
1
Order By: Relevance
“…Oloveira's study concluded that 1% w/v zinc acetate in drinking water for 60 days caused learning impairment in mice 24. The result of the MWM test confirms the inability of the rats in the 464 and 1000 mg per kg bwt groups to swim in the correct quadrant, this may be due to the decrease in cognitive function and memory loss.…”
Section: Discussionmentioning
confidence: 82%
“…Oloveira's study concluded that 1% w/v zinc acetate in drinking water for 60 days caused learning impairment in mice 24. The result of the MWM test confirms the inability of the rats in the 464 and 1000 mg per kg bwt groups to swim in the correct quadrant, this may be due to the decrease in cognitive function and memory loss.…”
Section: Discussionmentioning
confidence: 82%
“…This confirms severe spatial memory impairment in lead compartment than the control group and also they spent less time in the bright compartment indicating lead induced memory impairment. De Oliveira et al [26] found that rats exposed to low level of lead from the gestation day 11 till the postnatal day 28 had significantly reduced latency values in the step-through inhibitory avoidance memory task. In a study conducted by Moreira et al [27], rat pups exposed to lead acetate during PG, G, L and GL group of rats spent less time, and traveled a short distance in the target quadrant during the water maze test indicating spatial memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Excess dietary zinc leads to copper deficiency which can produce impairments in cognition. Chronic postnatal intoxication with zinc did not interfere with the exploratory behaviour and did not alter memory retention in an inhibitory avoidance model in mice [24]. Moreover, rats supplemented pre- and postnatally with zinc carbonate demonstrated a lack of extinction to the tone in cued fear conditioning [25].…”
Section: Discussionmentioning
confidence: 99%